A high-resolution in situ X-ray diffraction study of mineral transitions due to post-hydration heating in CM chondrite meteorites - Laura E. Jenkins; Ashley J. King; Martin R. Lee; Luke Daly; Stephen P. Thompson; Sarah J. Day; Lucy Saunders; Pierre-Etienne Martin; Fahkri Bintang (Earth, Planets and Space, 2024)
Abstract The effects of post-hydration heating over a broad range of temperatures are evident in many Mighei-like carbonaceous (CM) chondrites as a variety of mineral transitions. To better understand these processes and how a CM chondrite’s starting composition may have affected them, we experimentally heated two meteorites with different degrees of aqueous alteration, Allan Hills 83100 and Murchison, at 25 °C temperature steps from 200 °C to 950 °C and 300 °C to 750 °C, respectively. During heating, synchrotron in situ X-ray diffraction patterns were collected. With the exception of calcite decomposition and its products, most mineral transitions were unaffected by starting composition. Key observations include: (1) partial decomposition of tochilinite at 200 °C, which indicates that tochilinite breakdown might be a two-stage process due to its intergrown layers of brucite/amakinite and mackinawite; (2) the breakdown of serpentine occurring at 300 °C with transitional phases appearing at 525 °C and 575–600 °C, while secondary olivine formed at 600 °C; (3) cronstedtite decomposing faster than lizardite, (4) the formation of secondary enstatite at 750 °C, and (5) calcite decomposition temperature differing significantly between meteorites, occurring at 725 °C and 575 °C in ALH 83100 and Murchison, respectively. The results for calcite are likely controlled by differences in its microstructure and chemical composition, related to the meteorite’s impact history and degree of aqueous alteration. The difference in calcite decomposition temperature also explains the contrasts in the observed breakdown products, with clinopyroxene occurring in both meteorites, and oldhamite only in ALH 83100. Mineral transitions due to post-hydration heating have been characterized with a high resolution XRD method, enabling a better understanding of processes occurring on the parent asteroids of CM chondrites. Graphical Abstract